Evaluation and Management of Hemorrhoids. Issue 4 (April 2020) - Jakubauskas, Matas; Poskus, Tomas
Abstract : Case Summary: A 46-year-old otherwise healthy female patient presents with bright red blood during defecation and a lump protruding on defecation that requires manual reduction. She is the mother of 2 children and has a long history of constipation.